Inventarisasi Dan Identifikasi Tumbuhan Air di Danau Hanjalutung Kota Palangka Raya - Ummi Suraya (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2019)
The aim of this research is to identify and to inventory water plants in Hanjalutung Lake,Petuk Ketimpun Village, Jekan Raya District, Palangka Raya City. This research was conducted from December 2017 to January 2018. Sampling was carried out in 3 (three) stations, namely inlet ,middle and outlet. The tool used for aquatic plants 2 x 2 m transect.The results of research aquatic plants found in the waters of Lake Hanjalutung 7 (seven) types namely Kiambang (Salvinia molesta), gerigit/bite (Leersia hexandra), Cat Tail Grass (Utricularia aurea), Para Grass (Cyperus platystylis), Water Hyacinth ( Eichhornia crassipes ), Kiapu (Pistia stratiotes) dan Ketanan (Polygonum sp).